2016
DOI: 10.1590/s1984-29612016085
|View full text |Cite
|
Sign up to set email alerts
|

Serosurvey of Borrelia in dogs, horses, and humans exposed to ticks in a rural settlement of southern Brazil

Abstract: The aims of the present study were to serosurvey dogs, horses, and humans highly exposed to tick bites for anti-Borrelia burgdorferi s.l. antibodies, identify tick species present, and determine risk factors associated with seropositivity in a rural settlement of Paraná State, southern Brazil. Eighty-seven residents were sampled, along with their 83 dogs and 18 horses, and individual questionnaires were administered. Immunofluorescence antibody test (IFAT) was performed on serum samples and positive samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Studies such as those by Melo et al 16 , by Montandon et al 17 , and Nascimento et al 18 , demonstrated that wild and domestic animals present serological evidence of infection by B. burgdorferi. Samples of dogs, horses, marsupials, rodents and opossums, analyzed in these studies, showed positive serology for antibodies anti-B.…”
Section: History Of the Disease And Epidemiologymentioning
confidence: 95%
See 1 more Smart Citation
“…Studies such as those by Melo et al 16 , by Montandon et al 17 , and Nascimento et al 18 , demonstrated that wild and domestic animals present serological evidence of infection by B. burgdorferi. Samples of dogs, horses, marsupials, rodents and opossums, analyzed in these studies, showed positive serology for antibodies anti-B.…”
Section: History Of the Disease And Epidemiologymentioning
confidence: 95%
“…The bacteria has a zoonotic cycle in which ticks of the type Ixodes 2 are usually included. But in Brazil, according to Gonçalves et al 2 and Mantovani et al 11 it was shown that these spirochetes are also present in ticks of the type Rhipicephalus, Amblyomma and Dermacentor (Figure 1), which transmit to dogs, horses, marsupials, rodents, opossums, cattle and humans 1,[16][17][18][19] . B. burgdorferi infects ticks when they feed on the blood of infected hosts 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Horbranz, Austria), a rabbit fluorescein isothiocyanateconjugated anti-sheep IgG and a rabbit fluorescein isothiocyanate-conjugated anti-sheep IgM (Sigma-Aldrich, St Luis, MO, USA). Titers ≥1:64 were defined as positive [81]. Slides were observed using a Nikon Eclipse E-400 fluorescence microscope (objective ×40).…”
Section: Indirect Immunofluerence Antibody (Ifa) Assaymentioning
confidence: 99%
“…In Brazil, studies have identified borreliosis in human patients with Brazilian Lyme-like disease or Baggio-Yoshinari syndrome (Yoshinari et al 2003, Mantovani et al 2012, and Borrelia burgdorferi sensu lato in asymptomatic humans (Gonçalves et al 2015) and ticks from the genus Dermacentor (Gonçalves et al 2013) [EB1]. Few reports relate to companion animals, and although anti-Borrelia antibodies have been found in dogs, to our knowledge the pathogen has not been isolated from sick dogs (Spolidorio et al 2010, Nascimento et al 2016 [EB1]. On that basis, there is currently no basis on which to justify introduction of a companion animal Borrelia vaccine to the region.…”
Section: Why Do We Not Have a Borrelia Vaccine In Our Country?mentioning
confidence: 99%
“…, Nascimento et al . ) [EB1]. On that basis, there is currently no basis on which to justify introduction of a companion animal Borrelia vaccine to the region.…”
Section: Frequently Asked Questionsmentioning
confidence: 99%